Secondary school factors relating to academic success in first-year Health Science students - Naidoo, Urisha; Flack, Penelope Susan; Naidoo, Indirani; Essack, Sabiha Yusuf (South African Journal of Higher Education, 2018)
Universities in South Africa, experience challenges related to throughput rates, especially in the first year of study. Student dropout in the School of Health Sciences (SHS) negatively affects the enrolment targets with the concomitant loss of student subsidy and fees as well as the number of prospective health care professionals who are required to address the shortage of skilled health care workers in the country. This thus emphasizes the need to determine secondary school factors that relate to success and throughput in the first year of study, viz., area and type of schooling, matriculation point scores and matriculation subject choices. A retrospective design with a quantitative approach was used to collect data from a total of 713 student records over the period 2009-2011. Quantitative data were analysed using descriptive and inferential statistics while the Spearman Rank-order correlation test and the Mann-Whitney test were used to determine differences among variables related to academic success. A p-value of ?0.05 was considered statistically significant. Data was analysed and presented as annual composite results as well as stratified by disciplines. Overall the area of secondary schooling did not statistically significantly correlate with academic success. In contrast, the type of secondary schooling (p=.012), matriculation points (p=.000) and all matriculation subjects investigated (p<.005) were statistically significant variables that correlated with academic success. At discipline-level, Physiotherapy showed to have the most consistent correlations among variables, with a moderate correlation with matriculation subjects as well as the APS. The results of this study yielded evidence-based admissions criteria for students into the SHS at the University of KwaZulu-Natal (UKZN).